Puristic tendencies in modern terminology studies - Кримець, Оксана Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyzes modern puristic tendencies in the formation of terms. Language purism is one of the terminology development factors not only in the Ukrainian language, but also in a lot of European languages, as it provides the development of national terminology, the use of self-linguistic resources, which are a matter of course. The connection between the purism and the development of society, another level of its manifestation with respect to certain historical events are considered here; positive and negative aspects of purism are distinguished. Three waves of Ukrainian poetry, characterized by a different level of extreme and moderate purism, gave great experience for the development of terminology. The views of modern linguists on the purification of Ukrainian scientific and technical terminology in the conditions of globalization of society and science are described. The moderate and positive influence of modern puristic tendencies aimed at the restoration of autochthonous word-formation processes in Ukrainian terminology, which promotes national priorities in the formation of terms, is emphasized.